Preparation method for synthesizing formamidine cesium-based perovskite nanocrystals based on solution method

Through the synthesis method of formidine cesium-based perovskite precursor based on the aqueous phase method, the problem of perovskite solar cell materials being easily degraded in harsh environments is solved, and the preparation of high-purity nanocrystals is realized, the process is simplified and the cost is reduced.

CN119843363APending Publication Date: 2025-04-18CHENGDU UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510075937.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Perovskite solar cell materials are prone to deterioration and decomposition under high temperature, humidity, oxidation and other environments, resulting in reduced service life and performance. The preparation process is complex and costly, making it difficult to ensure the purity of the material and remove impurities.

Method used

The synthesis method of cesium-based perovskite precursor based on the aqueous phase method was adopted. High-purity cesium-based perovskite nanocrystals were prepared by adding europium acetate, cesium acetate and formica acetate to the aqueous hydroiodic acid solution, and after stirring and filtration.

Benefits of technology

The conditional control costs and environmental pollution impacts in the perovskite production process are reduced, and the nanocrystals are prepared have good performance, few impurities, and have good optical properties, which simplifies the preparation process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843363A_ABST
    Figure CN119843363A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method for synthesizing formamidine cesium-based perovskite nanocrystals based on a solution method, and belongs to the field of new energy. The invention provides a high-purity FAxCs1-xPbI3 perovskite nanocrystal which is prepared from formamidine acetate (FAAc), cesium iodide (CsI), cesium acetate (FACs), lead acetate (PbAc2) and hydroiodic acid (HI) in a room-temperature aqueous solution in the air. The method comprises the following steps: 1) preparing a hydroiodic acid aqueous solution with a certain pH value; (2) sequentially putting lead acetate, cesium acetate and formamidine acetate crystals into the solution, and fully stirring; (3) after full reaction, carrying out suction filtration to obtain a solid matter, and washing with ethyl acetate; and 4) placing the obtained product in a tubular furnace for vacuum drying. The formamidine cesium-based perovskite nanocrystal prepared by the invention has few impurities, can be used as a precursor solute for preparing a perovskite solar cell, is beneficial to accurately controlling the stoichiometric ratio of each component in the precursor solution, and can be used for preparing an organic-inorganic hybrid perovskite solar cell light absorption layer with better crystallization performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solar cells and preparation methods thereof, in particular to a preparation method of formamidinium cesium-based perovskite based on an aqueous phase method. Background Art

[0002] As a new type of energy, solar energy has received more and more attention in the current environment where global energy depletion, environmental pollution and other issues are becoming increasingly prominent. Solar cells can directly convert solar energy into electrical energy, which is inexhaustible and occupies an important position in the field of renewable energy generation. At present, solar cells have evolved from the first generation represented by crystalline silicon solar cells, experienced the second generation of thin-film solar cells, and have developed to the third generation of advanced and efficient new solar cells using nanotechnology, such as perovskite solar cells. Perovskite solar cells have developed rapidly. Since the first report in 2006, the highest efficiency of perovskite solar cells has reached 26.7%. Perovskite light-absorbing materials have excellent properties such as strong light absorption, high carrier mobility, and small exciton binding energy, and have become a research hotspot in the field of third-generation solar cells.

[0003] Cesium formamidinium perovskite has good phase stability and an ideal band gap, but when the Cs ion concentration is low (≤20%), the alloying process of the material will undergo a complex intermediate phase transition process. Due to the difference in radius between FA ions and Cs ions, this process will cause lattice distortion in the material, destroying the material morphology and its corresponding structural properties. Based on this, the preparation of high-quality cesium formamidinium perovskite light absorbing materials is a prerequisite for the preparation of high-performance perovskite solar cells.

[0004] It is true that perovskite light absorbing materials have excellent photovoltaic properties, but there are still many process difficulties that need to be overcome in the preparation of perovskite solar cells. For example, perovskite light absorbing materials are very prone to degradation and decomposition in high temperature, humidity, oxidation and other environments, which will significantly reduce their service life and device performance; and the preparation process of high-quality perovskite solar cell devices is cumbersome and costly, and it is difficult to ensure the purity of the materials and effectively remove impurities. Therefore, overcoming the environmental sensitivity of the perovskite material preparation process and simplifying the preparation process can significantly reduce the preparation cost of perovskite solar cells and help accelerate the commercialization and popularization of perovskite solar cells.

[0005] In the present invention, we sequentially add a certain stoichiometric ratio of lead acetate, cesium acetate, and formamidine acetate to a certain proportion of hydroiodic acid aqueous solution, and obtain formamidine cesium-based perovskite nanocrystals with low impurity content through a simple preparation process under normal temperature and air conditions, which can be used as a precursor of subsequent perovskite solar cell thin film materials, thereby reducing the condition control cost and environmental pollution impact in the perovskite production process. The novelty of the present invention is that it adopts a new method for synthesizing formamidine cesium-based perovskite precursors. The microcrystals synthesized by this method have high purity and can be directly dissolved in DMF / DMSO solution as a precursor of subsequent solar cell light absorption materials. It has the advantages of simple preparation, uniform product, and high purity. Summary of the invention

[0006] In order to prepare cesium formamidinium-based perovskite nanocrystals with expected performance, the present invention provides a method for preparing perovskite microcrystals for perovskite solar precursors based on aqueous phase synthesis.

[0007] To achieve the above object, the present invention adopts the following technical solutions: Step 1: The filter, drug bottle, and magnet used in the experiment were ultrasonically cleaned with deionized water, isopropanol, and anhydrous ethanol in turn, each step for 15 min, and repeated twice, and then placed in a drying oven to dry. After drying, they were sealed with sealing film to prepare for subsequent work.

[0008] Step 2: Weigh in a glove box with humidity and oxygen content below 0.01 ppm to ensure that the molar ratio of cesium acetate, formamidine acetate, lead acetate, and hydroiodic acid is 0.001-3:0001-5:0.001-5:0.001-7.2. Take an appropriate amount of deionized water to prepare an aqueous solution of hydroiodic acid to ensure that the pH value of the solution is less than 3. First, add lead acetate to the solution and stir at 100 rpm for 10 minutes to ensure that the lead acetate reacts completely first. Then add cesium acetate and then formamidine acetate. After ensuring that the pH value of the solution is less than 3, increase the speed to 700 rpm and continue stirring for 12 hours until the reaction is complete.

[0009] Step 3: Place a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm into a suction filtration device and wet it with ethyl acetate. Filter the suspension obtained in step 2, take it out and put it into a new medicine bottle containing ethyl acetate and stir for 10 min. After repeating five times, transfer the obtained solid to a tube furnace, purge the tube furnace with nitrogen five times, and then evacuate it, keep the pressure gauge reading stable at -0.1 Mpa, set the heating rate to 5℃ / min, the insulation temperature to 55℃, and the insulation time to 36 h. After completion, good quality cesium formamidinium perovskite nanocrystals can be obtained.

[0010] The present invention has the following advantages and beneficial effects: the preparation process is mostly carried out under a conventional atmospheric environment, reducing the cost of controlling environmental conditions; the solvent used in the preparation has low toxicity and little pollution to the environment; the prepared nanocrystals have good performance, small impurities, and good optical properties; the experimental steps are simple and can be prepared on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 is the FA prepared in the present invention x Cs 1-x XRD characterization results of PbI3 perovskite nanocrystals.

[0012] Figure 2 is the FA prepared in the present invention x Cs 1-x SEM characterization results of PbI3 perovskite nanocrystals.

[0013] Figure 3 is the FA prepared in the present invention x Cs 1-x EDS characterization results and Mapping analysis results of PbI3 perovskite nanocrystals. Figure 3 A is for FA x Cs 1-x EDS characterization results of PbI3 perovskite nanocrystals, Figure 3 B, C, D, E, F, G are FA x Cs 1- x Mapping analysis results of C, H, O, I, Cs, and Pb elements of PbI3 thin film.

[0014] Figure 4 is the FA prepared in the present invention x Cs 1-x UV-vis absorption spectrum and band gap characterization results of PbI3 perovskite nanocrystals.

[0015] Figure 5 is the FA prepared in the present invention x Cs 1-x Band gap characterization results of PbI3 perovskite nanocrystals.

[0016] Figure 6 is the FA prepared in the present invention x Cs 1-x Steady-state fluorescence emission spectrum characterization results of PbI3 perovskite nanocrystals.

[0017] Figure 7 is the FA prepared in the present invention x Cs 1-x FTIR characterization results of PbI3 perovskite nanocrystals.

[0018] Figure 8 is the FA prepared in the present invention x Cs 1-x Schematic diagram of the experimental process of PbI3 perovskite nanocrystals, including weighing, mixing, stirring, filtering, and drying steps. DETAILED DESCRIPTION

[0019] The present invention will be further described below in conjunction with the attached embodiments.

[0020] Example 1: FA x Cs 1-x Preparation of PbI3 perovskite nanocrystals (1-1) Cleaning before preparation Prepare several medicine bottles, filtration devices, and magnetic particles, and perform ultrasonic cleaning on them with deionized water, isopropanol, and anhydrous ethanol, respectively, for 15 min each step, and repeat twice, and then place them in a drying oven to dry. After drying, seal them with sealing film and store them for later use.

[0021] (1-2) FA x Cs 1-x Preparation of PbI3 perovskite nanocrystal reaction solution In a glove box, weigh 0-1000 mg of formamidine acetate (FAAc), 0-1000 mg of cesium acetate (CsAc), and 0-10 g of lead acetate trihydrate (PbAc·3H2O). Under air, weigh 0-30 g of hydroiodic acid (HI, 47 wt%) and 1 mL of deionized water.

[0022] Add hydroiodic acid and deionized water to the drug bottle with a magnet, place it on a magnetic stirrer and start stirring at 100 rpm and immediately cover the drug bottle with tin foil. First add lead acetate and continue stirring for 10 minutes. After confirming that the reaction is sufficient, slowly add cesium acetate, and then slowly add formamidine acetate. After all the drugs are added, increase the speed uniformly and slowly to 700 rpm and continue stirring for 12 hours.

[0023] (1-3) FA x Cs 1-x Extraction of PbI3 perovskite nanocrystals Place a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm in a suction filtration device and wet it with ethyl acetate. Filter the suspension obtained in step (1-2), take it out and put it into a new medicine bottle filled with ethyl acetate and stir it for 10 min. After repeating five times, transfer the obtained solid to a tube furnace, purge the tube furnace with nitrogen five times, and then evacuate it to keep the pressure gauge reading stable at -0.1 Mpa. Set the heating rate to 5℃ / min, the insulation temperature to 55℃, and the insulation time to 36 h.

[0024] (1-4) FA x Cs 1-x Characterization of PbI3 Perovskite Nanocrystals FA prepared by the present invention x Cs 1-x The characterization diagram of PbI3 perovskite nanocrystals is shown in the attached figure.

[0025] Depend on Figure 1 FA prepared by the present invention x Cs 1-x The XRD pattern of PbI3 perovskite nanocrystals conforms to the characteristics of the standard card PDF#01-084-2966 of FAPbI3, indicating that the prepared FA x Cs 1-x PbI3 perovskite nanocrystals have no impurities, and their half-peak width is small and the peak intensity is high, indicating that the prepared FA x Cs 1-x PbI3 perovskite nanocrystals have high crystallinity and good orientation. 1-x Cs x The position of the diffraction peak of PbI3 is slightly shifted to a higher angle compared to the position of the FAPbI3 peak, indicating that the Cs+ ions have been successfully introduced into the perovskite lattice to complete the alloying and slightly widen its band gap.

[0026] Depend on Figure 2 ,From the SEM images of the samples, it can be seen that the grains are mostly rod-shaped, small in size and more ,uniformly distributed, showing a highly dense and uniform surface morphology ,structure.

[0027] Depend on Figure 3 A. The EDS spectrum of the sample shows that there are corresponding FA in the sample x Cs 1-x The elements of PbI3 are Figure 3 From the B, C, and D figures, we can see that the C, N, and O elements are evenly distributed in the FA. x Cs 1-x In PbI3 perovskite film, C, N, and O elements belong to the FA group, indicating that FA is evenly distributed in FA. x Cs 1-x On PbI3 perovskite film; Figure 3 From the E, F, and G figures, we can see that the Cs, Pb, and I elements are evenly distributed in the FA x Cs 1-x PbI3 perovskite film. This indicates that FA was successfully synthesized. x Cs 1-x PbI3 perovskite nanocrystals.

[0028] Depend on Figure 4 , Figure 5 It can be seen from the UV absorption visible light spectrum that the prepared nanocrystals have good light absorption ability in the range of 200~600 nm. The band gap of the nanocrystals calculated by the electron transition formula is 1.45 eV, which is consistent with the theoretical optical band gap of 1.45 eV.

[0029] Depend on Figure 6 The photoluminescence spectrum shows that it has peaks at 714 nm and 756 nm, indicating that its fluorescence emission intensity is high and its fluorescence lifetime is long, which will reduce the recombination of photogenerated carriers and improve the photoelectric properties of the material. Depend on Figure 7 The FTIR spectrum shows that the sample has 8 peaks, which correspond to different chemical bond vibrations. The stretching vibration of the NH bond is at 3400 cm -1 The stretching vibration of CH is at 3255cm -1 The peaks are generated at 1710 cm-1, and the stretching vibration of C=N is at 1710 cm-1. -1 The stretching vibration of NH is at 1610 cm -1 The stretching vibration of CH is at 1350cm -1 A peak is produced at 1113 cm-1, and CN stretching vibration is at 1113 cm-1. -1 This indicates the presence of the formamidine group and that the impurities such as acetate and ethyl acetate in the product have been completely removed.

[0030] The above descriptions are merely embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent transformation using the contents of the present invention's specification and drawings, or direct or indirect application in other related technical fields, are also included in the patent protection scope of the present invention.

Claims

1. A method for preparing cesium formamidinium-based perovskite nanocrystals based on a solution method, characterized by the following steps: (1) Weigh corresponding amounts of hydroiodic acid, cesium acetate, formamidine acetate, and lead acetate and mix them thoroughly with an appropriate amount of deionized water to allow complete reaction; (2) After the reaction is complete, the suspension of (1) is filtered and washed thoroughly; (3) The washed product is placed in a tube furnace and heated under vacuum to dry. After drying, FA is obtained. x Cs 1-x PbI3 perovskite nanocrystals.

2. The method for preparing cesium formamidinium-based perovskite nanocrystals based on a solution method according to claim 1, characterized in that: In step (1), the molar ratio of cesium acetate, formamidine acetate, lead acetate and hydroiodic acid is 0.001-3:0001-5:0.001-5:0.001-7.2, and the weighing is performed in an environment with humidity and oxygen content less than 0.01 ppm (in a glove box). The product obtained in step (3) is dried in a vacuum environment (in a tube furnace), and the remaining steps are performed in a normal air environment.

3. A method for preparing cesium formamidinium-based perovskite nanocrystals based on a solution method as claimed in claim 1, characterized in that: First, wrap the container of hydroiodic acid aqueous solution with tin foil to prevent hydroiodic acid from decomposing. When mixing the drug with the solution, first add lead acetate and stir for 10 minutes until it is completely dissolved, then add cesium acetate and formamidine acetate. The overall pH value of the solution should be between 0-7 during the whole process.

4. The method for preparing cesium formamidinium-based perovskite nanocrystals based on a solution method according to claim 1, characterized in that: The medicine bottles, magnets, and sand core filters used in steps (1), (2), and (3) are ultrasonically cleaned with deionized water, isopropanol, and anhydrous ethanol in turn, and then placed in a drying oven for heating and drying before use.

5. The method for preparing cesium formamidinium-based perovskite nanocrystals based on a solution method according to claim 1, characterized in that: Step (1) The solution is stirred using a magnetic stirrer and a magnet. When lead acetate is added, the rotation speed is 100 rpm. When cesium acetate and formamidine acetate are added, the rotation speed is slowly increased to 800 rpm and stirring is maintained for 12 hours.

6. The method for preparing cesium formamidinium-based perovskite nanocrystals based on a solution method according to claim 1, characterized in that: In step (2), filtration is performed using a polytetrafluoroethylene filter membrane with a pore size of 0.22 μm. The solid matter obtained by filtration is yellow and does not adhere to the bottle wall or the filter paper.

7. The method for preparing cesium formamidinium-based perovskite nanocrystals based on solution synthesis according to claim 1, characterized in that: The washing solution used in step (2) is ethyl acetate, and the washing and filtration times are 5 times. After the first four filtrations, the mixture is placed back in ethyl acetate and stirred for 10 minutes. During the last washing, the solution becomes colorless and there is no attachment on the bottle wall.

8. The method for preparing cesium formamidinium-based perovskite nanocrystals based on a solution method according to claim 1, characterized in that: After the sample is placed in the tube furnace in step (3), the tube furnace is first purged with nitrogen five times, and then evacuated to keep the pressure gauge reading stable at -0.1 MPa. The tube furnace is set to a heating rate of 5°C / min, a holding temperature of 55°C, and a holding time of 36 h.